2014
DOI: 10.1111/1471-0528.12707
|View full text |Cite
|
Sign up to set email alerts
|

Verification of the anatomy and newly discovered histology of the G‐spot complex

Abstract: Objectives To expand the anatomical investigations of the G‐spot and to assess the G‐spot's characteristic histological and immunohistochemical features. Design An observational study. Setting International multicentre. Population Eight consecutive fresh human female cadavers. Methods Anterior vaginal wall dissections were executed and G‐spot microdissections were performed. All specimens were stained with haematoxylin and eosin (H&E). The tissues of two women were selected at random for immunohistochemical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…In comparison with the measurements presented in the study of Ostrzenski et al, significant differences were observed pertaining to the distance of the urethral meatus to the G‐spot complex, its height and thickness. Table compares our key anatomical findings with those of Ostrzenski et al…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…In comparison with the measurements presented in the study of Ostrzenski et al, significant differences were observed pertaining to the distance of the urethral meatus to the G‐spot complex, its height and thickness. Table compares our key anatomical findings with those of Ostrzenski et al…”
Section: Resultsmentioning
confidence: 53%
“…The question of whether the G‐spot does exist has raised controversy ever since it was announced. The long‐lasting lack of profound anatomical, physiological and imaging evidence for its existence has been addressed in recent times in part by the dissectional study of Ostrzenski et al, whose descriptions motivated us as radiologists to investigate their findings with up‐to‐date MRI modalities; a literature research concerning MRI‐based evidence for the existence of the G‐spot yielded no satisfactory results . We were able to identify a morphological entity in our MRI exams with a consistent and reproducible signal quality in T1‐ and T2‐weighted sequences in the majority (>60%) of patients that was correlated with the descriptive anatomical measurements of Ostrzenski et al…”
Section: Discussionmentioning
confidence: 75%
“…Some years ago it was proven that the G‐spot does not exist, but is the female prostate, located in the pelvic urethra, therefore Ostrzenski et al . have not described the G‐spot, the ‘G‐spot complex’ is an incorrect term without scientific basis, and there are no MRI images of the G‐spot because it does not exist.…”
Section: A Rebuttal: the G‐spot Does Not Existmentioning
confidence: 99%
“…More recently, Ostrzenski et al. asserted anatomical proof of the G‐spot through dissections of eight Caucasian cadavers [54]. The tissues were stained with hematoxylin and eosin, and two additional specimens underwent immunohistochemical staining.…”
Section: The Clitoris and Vaginal Eroticismmentioning
confidence: 99%